Synchronicity: did Jung have it right? - Forrer, Kurt (International Journal of Dream Research, 2015)
1. The Problem or the Day of the Tooth: Description of a synchronistic event from personal experience. It is a puzzling experience the observation of which requires a certain alertness of mind. It took Jung twenty years to pluck up enough courage to make his thoughts on this matter public. Jung proposed an ‘acausal law’ that was to form together with the triad of space, time and causality a ‘quaternio’. This would have to make science even more uncertain than Schrödinger’s cat. The Celestine Prophecies refer to this phenomenon as ‘insights’ with a spiritual bias. Stripped of its bias it turns out to be mindfulness possessed by different individuals to varying degrees. 2. Day of the Fishes: Jung’s example of serial synchronicity. He admits that it is a difficult subject that requires an open mind. Six fish motifs appear within 24 hours. His attempts of explaining the phenomenon. 3. The Scarab Incident: The classic synchronistic event that leads Jung to explain this occurrence as the workings of an ‘acausal connecting principle’. The occasion that gave birth to the synchronicity principle was the apparent accidental appearance of an European scarab while one of Jung’s patients was telling him her dream in which she was given a piece of jewellery in form of a gold-green scarab. Jung fails to see the obvious yet comes ever so close to the real explanation. He states that such synchronicities are often accompanied by a kind of foreknowledge. 4. Foreknowledge in Dreams and Waking. Jung realises that such foreknowledge can come from our dreams. But, so he argues, it may also come in the waking state. He fails to see that foreknowledge can only come from dreams. When it comes in waking it is nothing more mysterious than a dream remembered ‘cryptomnesically’. This must be examined more closely. 5. The Déjà Vu: Jung discovered that this experience is rooted in a dream. The déjà vu is the classic example of a dream come true. There are two variants of the déjà vu: one is based on a cryptomnesic recall of a dream, the other on a direct recall of a precursory dream. 6. Speak of the Devil: The description of this occurrence explains the cryptomnesic recall of a dream. It simply means the ability to recall the content of a dream without being able to detect the source of this knowledge. This is no different to recalling that Canberra is the capital of Australia without remembering where and when we had learnt this fact. It also demonstrates that foreknowledge or premonition is dream based. 7. The Broken Dream: The exclamation ‘you have broken my dream!’ explains that dreams may be recalled in course of conversations that touch upon the central motif of the dream. Speaking of babies, for instance, will recall the dream of this morning in which a baby figured as the highlight of the dream. 8. The Scarab Dream revisited: The synchronistic mystery of the scarab dream and its materialisation in Jung’s clinic is explained in terms of the “Speak of the Devil Syndrome”. 9. Return to the Day of the Fishes: The serial synchronicities of the fish motif are explained: a precursory dream spawned the recurrence of the fish motif. Jung did not realise that the main motif of a dream manifests serially. Once he went along with Kammerer who believed that there was such a thing as a law of seriality. Jung rejects this later as nothing more than a statistical problem. The serial manifestation of a dream engenders serial synchronicities. 10. The Serial Manifestation of Dreams. The V-dream from my book “Pregrams of Tomorrow” is provided as an example. 11. The Royal Road to the Unconscious. Freud’s assertion that our conscious as well as our unconscious life is determined by the Unconscious. Freud can’t prove this since he denies that the dream can see the future. He is unclear about the function of the dream. He only knows that it is the mirror of the Unconscious that determines our ways. He cannot come to the conclusion that the dream is a picture of the future because he believes that the dream can only picture the past. Freud remains confused. Logic can provide the crucial answer. Confusion of the masters tends to block the understanding of the followers. 12. The Star Witness to the Dream’s Anticipatory Nature. The case of Michael Barnsley, a mathematician and inventor of the image compression soft ware. He had a nightmare for 20 years, which formed the basis of his eventual invention. He did not realise this until 20 years after the first nightmare. This is evidence that the dream leads and knows the whole story whereas the dreamer will be unaware of what is brewing in his Unconscious. 13. Experimental Corroboration of the Dream’s Anticipatory Nature. According to a report in “The New Scientist” of 14th September 2002, Benjamin Libet of the California University experiments with brain functions and discovers that our actions are motivated unconsciously. Freud’s assertion is vindicated. My finding that the dream is the template of waking experience is underpinned. 14. The Experiment of the Posthypnotic Suggestion. The posthypnotic suggestion takes place under similar conditions as the nocturnal dream. It can serve therefore as an illustration of how the dream dictates to us what to do in a similar way as does the hypnotist. The result tallies with what John Gray said who had penned the article on Libet’s experiment: “If cognitive science is right, the picture of humans that philosophers conjure up when defending the ideal of personal autonomy is at least partly a chimera.” 15. Determinism as the Solution to the Riddle of Synchronicity. In view of strong evidence that the dream is the precursor of waking, synchronicity is no longer a mystery, but becomes simply a series of déjà vus. 16. Causality versus the Acausal Connecting Principle of Jung. Everything points to the fact that synchronicity is not an acausal connecting principle but an ‘ordinary’ linking of ‘ordinary’ causal events. What is different is that the brain function that induces a physical action remains hidden until it is exposed experimentally. 17. Return to the Day of the Tooth 18. Extension of the Causal Chain. Causality is led back from the 3rd dimension of every day life to the 4th dimension of the dream and ultimately to the 5th dimension of the Pre-existent Reality. 19. Time and Space. The dream as the best illustration that time and space are illusory. Causality as the ultimate casualty. 20. Galileo II A changed way of seeing the world. From the geocentric to egocentric. 21. The Unitive Vision